High-strength high-toughness modified para-aramid fiber and preparation method thereof
By introducing chlorine-containing diamine monomers in block copolymerization in heterocyclic aramid fibers and initiating coupling reactions by heat treatment, the problem of difficulty in improving strength and toughness in the prior art is solved, and high strength, high toughness and goodness are achieved Preparation of modified fibers with composite properties.
Patent Information
- Application Number
- CN202411475598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art is difficult to improve the strength and toughness of heterocyclic aramid fibers at the same time. Commonly used modification methods will cause the tensile strength to decrease when improving toughness, or the toughness is not high when increasing strength, and increasing molecular weight will affect the spinning ability. .
The chlorine-containing diamine monomer is introduced into the heterocyclic aramid structure in the form of block copolymerization through the traditional 'two-pot method', and the polymerization ratio between the chlorine-free block and the chlorine-containing block is regulated, and the chlorine side in the heat treatment is used The removal of the matrix triggers the coupling reaction between the macromolecules and chains to extend the chain, increase the molecular weight and maintain the motility of the molecular chain.
It significantly improves the tensile strength and elongation of breaking heterocyclic aramid fiber, and the toughness is increased to 100~130MJ/m3, while improving the composite performance, with tensile strength of 33~40cN/dtex and elongation of breaking 4.5~8.0% , and maintains the good composite properties of the fiber.
Smart Images

Figure CN119265732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of para-aramid preparation, and in particular to a high-strength and high-toughness modified para-aramid fiber and a preparation method thereof. Background Art
[0002] As a typical high-performance organic fiber, para-aramid is widely used in aerospace, national defense, automotive electronics, sports equipment and other fields. Heterocyclic aramid is a modified para-aramid prepared by copolymerizing the structure of para-aramid (PPTA) with an asymmetric benzimidazole ring structure. The regularity of its molecular chain is reduced, but the tensile strength is higher, which has attracted a lot of attention. Compared with organic fibers such as PPTA and PBO, and inorganic fibers such as carbon fibers, heterocyclic modified para-aramid has better comprehensive strength and toughness. Therefore, heterocyclic aramid has important applications in the field of impact-resistant materials, especially as bulletproof materials and rubber reinforcement materials. With the development of modern industrial technology, it is necessary to further improve the strength and toughness of heterocyclic aramid. However, there is an essential contradictory relationship between strength and toughness, and improving the strength and toughness of heterocyclic aramid at the same time faces huge challenges.
[0003] To improve the toughness of heterocyclic aramid, it is first necessary to improve its fracture resistance, that is, to increase the elongation at break. The commonly used method is to introduce meta-connections, flexible structures and side groups into its molecular structure to destroy the rigidity and regularity of the molecular chain, reduce the crystallinity and orientation of the fiber, and increase the deformation ability of the fiber under stress. Although the elongation at break of the fiber can be improved by these modification methods, its tensile strength will be significantly reduced, and the final toughness will not be improved. The Chinese patent with application number 202010402998.3 discloses a high-strength and high-elongation heterocyclic aromatic polyamide fiber and its preparation process, which specifically discloses modification methods such as introducing chlorine side groups, cyanide side groups, isophenyl structures and ether bonds into the heterocyclic aramid molecular chain. The elongation at break of the prepared heterocyclic aramid can reach 4.5-10.0%, but its tensile strength is not improved. The Chinese patent application number 201410656733.0 discloses a chlorine-containing high-performance heterocyclic aromatic fiber and its preparation method and application. It specifically discloses that the chlorine side groups are introduced into the heterocyclic aromatic fiber molecular chain for modification, which increases the adhesion between the fiber and the epoxy resin, but the tensile strength and elongation at break of the fiber are not high, the tensile strength is 24-32 cN / dtex, and the elongation at break is 2.3-4.0%. The Chinese patent application number 201711091330.6 discloses a preparation method for chlorine-containing high-performance heterocyclic aromatic polyamide fiber. It specifically discloses that the chlorine side groups are introduced into the heterocyclic aromatic fiber molecular chain for modification, the surface activity of the modified fiber is improved and the flame retardancy is improved, and the limiting oxygen index is 30-50%, but its mechanical properties are not high, and the breaking strength is 3.50-5.0 GPa. In addition, the Chinese patent with application number 202110871051.1 also announced the introduction of chlorine side groups into the heterocyclic aramid molecular chain for modification, and the preparation of modified fibers by copolymerization of p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, 4,4'-diamino-2'-chloro-benzoylanilide and terephthaloyl chloride. The composite properties of the modified fiber and epoxy resin have also been improved, the tensile strength of the dipped yarn is 5.0-6.5GPa, and the breaking strength of the dry yarn is 27-36cN / dtex, but the elongation at break of the fiber is only 2.5-4.2%, and the toughness is not high. The Chinese patent application number 201710694853.3 discloses high-strength aromatic copolyamide fibers and their preparation methods, which specifically discloses the introduction of cyano side groups into the heterocyclic aramid molecular chain for modification, and the prepared fibers have a tensile strength of 3.5-5.5 GPa, but a breaking elongation of only 2.5-4.5%. Therefore, it is not possible to simultaneously improve the strength and toughness of heterocyclic aramid fibers through simple chemical modification methods.
[0004] Another method to improve the fracture resistance of heterocyclic aramid is to increase its molecular weight. However, due to the large rigidity of the molecular chain of heterocyclic aramid and its limited solubility in composite solvents, increasing the molecular weight will cause the dynamic viscosity of the spinning solution to increase sharply, reduce the spinnability, and significantly reduce the mechanical strength. In order to increase the molecular weight of heterocyclic aramid without affecting the spinnability of its glue solution, Chinese patent application number 201710256235.0 discloses a method for preparing heterocyclic aramid fibers based on high-temperature post-chain extension reaction, which uses amino-terminated oligomers and carboxyl-terminated oligomers for blending and spinning, and uses amino and carboxyl groups to undergo condensation reaction at high temperature to increase the molecular weight of heterocyclic aramid in the later stage. However, this method greatly sacrifices the molecular weight of heterocyclic aramid in the polymerization stage, and the molecular weight growth in the later stage is limited, and the tensile strength of the prepared fiber only reaches 26-31 cN / dtex.
[0005] Existing preparation methods involving the modification of heterocyclic aramid fibers are all focused on improving the composite properties, mechanical strength and production efficiency of heterocyclic aramid fibers. However, there are few reports on solving the contradictory problem of simultaneously improving the strength and toughness of heterocyclic aramid fibers. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method for significantly improving the strength and toughness of para-heterocyclic aramid fibers at the same time, in view of the problem that the strength and toughness of existing para-heterocyclic aramid fibers are difficult to improve at the same time. An appropriate amount of chlorine-containing diamine monomer is introduced into the heterocyclic aramid structure in the form of block copolymerization by the traditional "two-pot method", and the polymerization degree ratio of the chlorine-free block to the chlorine-containing block is regulated at the same time. The chlorine side groups on the chlorine-containing block are removed during the heat treatment process to generate phenyl radicals, which triggers the local coupling reaction between the macromolecular chains to extend the chain, increase the molecular weight, and at the same time, the non-coupled chlorine-free block of appropriate length maintains the mobility of the overall macromolecular chain, thereby significantly improving the strength and toughness of the heterocyclic aramid.
[0007] To achieve the above object, on the one hand, the present invention provides a method for preparing high-strength and high-tenacity modified para-aramid fiber, which comprises the following steps:
[0008] S1. Under the protection of dry nitrogen, a diamine monomer is added to a lithium chloride N,N-dimethylacetamide composite solvent to dissolve, the reaction temperature is lowered to 0-10° C., and then terephthaloyl chloride equivalent to 75-97% of the diamine is added to react to obtain an amino-terminated chlorine-free block oligomer with a degree of polymerization of 7.0-65.7, wherein the diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole, or 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine;
[0009] S2, under the protection of dry nitrogen, adding the chlorine-containing diamine monomer to a lithium chloride N,N-dimethylacetamide composite solvent to dissolve, lowering the reaction temperature to 0-10° C., and then adding terephthaloyl chloride equivalent to 115-400% of the chlorine-containing diamine to react to obtain an acyl chloride-terminated chlorine-containing block oligomer with a degree of polymerization of 1.7-14.3, wherein the molar ratio of the chlorine-containing diamine to all diamines in steps S1 and S2 is 0.05-0.15;
[0010] S3, blending all the chlorine-free block oligomers of step S1 with all the chlorine-containing block oligomers of step S2, heating to 20-40° C. for reaction, to obtain a polymer solution having a solid content of 3-4.5 wt % and a dynamic viscosity of 30,000-100,000 centipoise at 25° C., wherein the polymerization degree ratio of the chlorine-free block oligomer to the chlorine-containing block oligomer is 4.0-9.0;
[0011] S4, subjecting the polymer solution of step S3 to a wet spinning process to obtain modified para-aramid precursor fibers, and then subjecting the precursor fibers to a static heat treatment at 340-380° C., or a continuous heat stretching treatment at 390-420° C., so that the degree of breakage and removal of the chlorine side groups is 7-20%, and finally preparing modified para-aramid fibers.
[0012] In the above steps S1 and S2, the amino group and the acyl chloride have high reaction activity and will release a lot of heat. In order to prevent local overheating and explosion, the reaction temperature is reduced to 0-10° C., more preferably 0-5° C. In addition, since the mixed solution in step S3 has a certain viscosity after the oligomers in steps S1 and S2 are blended, and the concentration of acyl chloride and amino end groups is not as high as that of directly adding monomers, it is necessary to heat it to 20-40° C. to promote sufficient reaction, and the temperature is more preferably 30-40° C.
[0013] The chemical structures of the above-mentioned 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine and terephthaloyl chloride are as follows:
[0014]
[0015] As a further preferred technical solution of the present invention, in step S1, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 0.65-0.95:0-0.25.
[0016] As a further preferred technical solution of the present invention, in steps S1 and S2, the mass fraction of lithium chloride in the N,N-dimethylacetamide composite solvent is 3-5%.
[0017] As a further preferred technical solution of the present invention, in steps S1 and S2, the total amount of terephthaloyl chloride added twice accounts for 0.995 to 1.005 of the total amount of diamines added in molar ratio.
[0018] As a further preferred technical solution of the present invention, the chlorine-containing diamine is at least one of 2-chloro-1,4-phenylenediamine, 2,5-dichloro-1,4-phenylenediamine, 3,3'-dichlorobenzidine, 2-chloro-4,4'-diaminobenzanilide, 2,6-dichloro-4,4'-diaminobenzanilide, 2-(2-chloro-4-aminophenyl)-5-aminobenzimidazole and 2-(2-chloro-4-aminophenyl)-5-aminobenzoxazole. Its chemical structure is as follows:
[0019]
[0020] As a further preferred technical solution of the present invention, in step S4, the static heat treatment process is carried out by vacuuming <200Pa, or introducing 0.5-5L / min nitrogen for protection.
[0021] As a further preferred technical solution of the present invention, in step S4, 0.5 to 5 L / min nitrogen is introduced for protection during the continuous hot stretching process.
[0022] As a further preferred technical solution of the present invention, in step S4, the tension of the continuous heat stretching is 0.05 to 0.5 cN / dtex.
[0023] According to another aspect of the present invention, the present invention also provides a modified para-aramid fiber, which is prepared by the above method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention introduces a chlorine-containing diamine monomer in the form of block copolymerization by a "two-pot method" on the basis of the diamine monomers 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine conventionally used in heterocyclic aramid, and the modified para-heterocyclic aramid has the characteristics of different block structures, including chlorine-free blocks and chlorine-containing blocks. The regularity of the chlorine-free block structure is better, and the regularity of the chlorine-containing block structure is reduced. By adjusting the length ratio of the two, the synergy of the two blocks can effectively transmit stress and convert energy, and can also avoid the influence of chlorine side groups on the overall regularity of the modified para-aramid macromolecules, thereby improving the orientation degree of the modified para-aramid.
[0026] (2) Due to the principle of "like dissolves like", the chlorine-containing blocks are more likely to aggregate, and the chlorine side groups on them break during the high temperature treatment process to generate phenyl radicals, and local coupling reactions occur between the macromolecular chains to extend the chains. Therefore, compared with the existing chlorine-containing heterocyclic aramid preparation technology, the present invention introduces a smaller amount of chlorine-containing diamine monomers, which can effectively cause the molecular weight of the modified heterocyclic aramid to increase during the heat treatment process.
[0027] (3) The present invention controls the polymerization degree ratio of the chlorine-free block and the chlorine-containing block to be 4.0-9.0, and the intermolecular coupling reaction only occurs in the chlorine-containing block. The non-coupled chlorine-free block of appropriate length maintains the mobility of the overall macromolecular chain, thereby achieving simultaneous improvement of the mechanical strength and toughness of the fiber.
[0028] (4) The present invention controls only 7-20% of the chlorine side groups to be removed during the heat treatment to initiate the coupling reaction and chain extension, which will not cause defects in the fiber. In addition, most of the remaining chlorine side groups increase the surface polarity of the fiber, so that the composite performance of the fiber is also significantly improved.
[0029] (5) The high-strength and high-tenacity modified para-aramid fiber prepared by the present invention has a tensile strength of 33-40 cN / dtex, an elongation at break of 4.5-8.0%, and a toughness of 100-130 MJ / m 3 , and has good composite properties, the strength of the dipped wire is 5.5~7.0GPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0031] Figure 1 The infrared spectra of the modified para-aramid raw yarn and the finished yarn after heat treatment in Example 1 of the present invention are shown in FIG. 1-raw yarn; 2-finished yarn after heat treatment.
[0032] Figure 2 This is a comparison chart of stress (cN / dtex)-strain (%) curves of the modified para-aramid fibers prepared in Example 1, Example 2 and Example 3 of the present invention, wherein the curves in the chart are: 1-Example 1; 2-Example 2; 3-Example 3.
[0033] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0036] During the preparation process of the high-strength and high-toughness modified para-aramid fiber proposed in the present invention, it is necessary to introduce chlorine-containing side groups into the macromolecular chain of heterocyclic aramid. Although the prior art (such as Chinese patents with application numbers 201410656733.0, 201711091330.6 and 202110871051.1) discloses the introduction of chlorine side groups into the molecular structure of hybrid aramid, thereby achieving the purpose of improving the composite properties, flame retardancy or strength of the fiber. However, the present invention provides a new preparation process and a chlorine-containing modified heterocyclic aramid with new structural characteristics to achieve a significant improvement in strength and toughness at the same time.
[0037] In the present invention, the control of block polymerization length is achieved by changing the feed ratio of diamine to acyl chloride, where r is the ratio of the number of amino groups to acyl chloride, or acyl chloride to amino groups in the reaction system, 0<r<1; p is the degree of reaction, and since the reaction activity of amino groups and acyl chlorides is very high, p≈1.
[0038]
[0039] In the present invention, the process of dechlorination of the chlorine side groups on the chlorine-containing block in the modified para-aramid fiber during heat treatment to induce a local coupling reaction and chain extension is as follows:
[0040] (1)
[0041] (2)
[0042] (3)
[0043] In the present invention, the degree of cleavage and removal of the chlorine side groups on the modified para-aramid molecular chain can be calculated by the change in the infrared absorption characteristic absorption peak intensity of the chlorine side groups before and after heat treatment. -1 is the infrared stretching vibration absorption peak of the C-Cl bond, I0 is the C-Cl bond absorption peak intensity of the modified para-aramid fiber, and I1 is the C-Cl bond absorption peak intensity of the modified para-aramid fiber after heat treatment.
[0044]
[0045] The technical solution for preparing high-strength and high-tenacity modified para-aramid fiber of the present invention is further described in detail below through specific examples.
[0046] Example 1
[0047] A. In the first reactor, under the protection of dry nitrogen, diamine monomers 2-(4-aminophenyl)-5-aminobenzimidazole (PABZ, 50.253 g) and p-phenylenediamine (PDA, 5.193 g) were added to a N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 3.5% in a molar ratio of 0.7:0.15, and stirred until the diamine was completely dissolved. The temperature in the reactor was lowered to 5°C, and then terephthaloyl chloride (TPC, 53.585 g) equivalent to 97% of the diamine was added at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 65.7;
[0048] B. In another reactor, under the protection of dry nitrogen, add 2-chloro-1,4-phenylenediamine (Cl-PDA, 6.846 g) to N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 3.5%, stir until the diamine is completely dissolved, lower the internal temperature to 5°C, and then add TPC (11.731 g) equivalent to 120% of Cl-PDA at one time. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer with a polymerization degree of 10.8 is obtained;
[0049] C. The molar ratio of the diamine monomers PABZ, PDA and Cl-PDA added in steps A and B is 0.7:0.15:0.15. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 30° C. and the reaction is continued for 2 hours to obtain a polymer solution with a solid content of 3.5 wt % and a dynamic viscosity of 73,000 centipoise at 25° C.
[0050] D. The polymer solution of step C is spun by conventional wet spinning. First, the solution is poured into a spinning storage tank for degassing and filtering. The solution is pressurized by 0.4 MPa nitrogen to enter a first coagulation bath with a mass ratio of water to N, N-dimethylacetamide of 1:1 through a metering pump and a spinneret (150 holes, 0.1 mm pore size) for coagulation and forming. The solution is drawn into a second coagulation bath with a mass ratio of water to N, N-dimethylacetamide of 5.6:1 for plasticization and stretching at a rate of 2.3. The solution is then washed, oiled, dried and wound into a tube to obtain a modified para-aramid precursor with a fineness of 480 ± 5 dtex. The precursor is placed in an atmosphere with a vacuum degree of 100 Pa, heated to 360° C. for static heat treatment for 40 min, and a modified para-aramid fiber is prepared.
[0051] from Figure 1It can be seen that the C-Cl bond infrared stretching vibration absorption peak intensity of the modified para-aramid fiber obtained in this embodiment is reduced after heat treatment compared with its original fiber, indicating that the content of chlorine side groups is reduced after heat treatment, because it is broken and removed to a certain extent during the heat treatment process, generating phenyl free radicals, thereby inducing local coupling reactions. The dechlorination degree of the modified para-aramid fiber is calculated to be 13%. The fiber properties are shown in Table 1.
[0052] Example 2
[0053] The modified para-aramid fiber prepared in Example 1 was used, except that in step D, the static treatment process was changed to static heat treatment at 400°C for 20 minutes, and finally a modified para-aramid fiber was prepared, and the dechlorination degree was 57%. The fiber properties are shown in Table 1.
[0054] Example 3
[0055] The modified para-aramid fiber prepared in Example 1 was used, except that in step D, the static treatment process was changed to static heat treatment at 320° C. for 30 min, to prepare modified para-aramid fiber with a dechlorination degree of less than 1%. The fiber properties are shown in Table 1.
[0056] Example 4
[0057] A. In the first reactor, under the protection of dry nitrogen, PABZ (58.317 g) and PDA (10.816 g) were added to a N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.5% in a molar ratio of 0.65:0.25, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 4°C, and then TPC (69.444 g) with an equivalent weight of 95% to the diamine was added at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 39.0;
[0058] B. In another reaction kettle, under the protection of dry nitrogen, add 3,3'-dichlorobenzidine (DCl-BPDA, 10.127 g) to N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.5%, stir until the diamine is completely dissolved, lower the internal temperature to 4°C, and then add TPC (11.777 g) equivalent to 145% of DCl-BPDA at one time. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer with a polymerization degree of 5.4 is obtained;
[0059] C. The molar ratio of the diamine monomers PABZ, PDA and DCl-BPDA added in steps A and B is 0.65:0.25:0.10. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 40° C. and the reaction is continued for 1 hour to obtain a polymer solution with a solid content of 4.5 wt % and a dynamic viscosity of 89,000 centipoise at 25° C.
[0060] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were subjected to continuous heat stretching treatment at 390° C. for 3 min, with a stretching tension of 0.5 cN / dtex and a nitrogen flow rate of 0.5 L / min, to prepare modified para-aramid fibers with a dechlorination degree of 8%. The fiber properties are shown in Table 1.
[0061] Example 5
[0062] A. In the first reactor, under the protection of dry nitrogen, PABZ (60.428 g) and PDA (4.371 g) were added to a N,N-dimethylacetamide composite solvent with a mass fraction of 5% lithium chloride in a molar ratio of 0.80:0.12, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 2°C, and then TPC (55.361 g) with an equivalent weight of 88% to the diamine was added at one time. After reacting for 0.7 h, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 15.7;
[0063] B. In another reactor, under the protection of dry nitrogen, 2-chloro-4,4'-diaminobenzanilide (Cl-DABA, 7.052 g) was added to a 5% lithium chloride N,N-dimethylacetamide composite solvent, stirred until the diamine was completely dissolved, the internal temperature was lowered to 2°C, and then TPC (13.020 g) equivalent to 238% of Cl-DABA was added at once. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer with a polymerization degree of 2.4 was obtained.
[0064] C. The molar ratio of the diamine monomers PABZ, PDA and Cl-DABA added in steps A and B is 0.80:0.12:0.08. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 20° C. and the reaction is continued for 3 hours to obtain a polymer solution with a solid content of 4.0 wt % and a dynamic viscosity of 54,000 centipoise at 25° C.
[0065] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were subjected to static heat treatment at 380° C. for 20 min under the protection of nitrogen at a flow rate of 5 L / min to obtain modified para-aramid fibers with a dechlorination degree of 16%. The fiber properties are shown in Table 1.
[0066] Example 6
[0067] A. In the first reactor, under the protection of dry nitrogen, add the diamine monomer PABZ (62.853 g) to the N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 3.5%, stir until the diamine is completely dissolved, lower the internal temperature to 0°C, and then add TPC (45.520 g) equivalent to 80% of the diamine at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution is obtained, and its degree of polymerization is 9.0;
[0068] B. In another reaction kettle, under the protection of dry nitrogen, add 2,6-dichloro-4,4'-diaminobenzanilide (DCl-DABA, 9.224 g) to N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 3.5%, stir until the diamine is completely dissolved, lower the internal temperature to 0°C, and then add TPC (17.702 g) equivalent to 280% of DCl-DABA at one time. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer with a polymerization degree of 2.1 is obtained;
[0069] C. The molar ratio of the diamine monomers PABZ and DCl-DABA fed in steps A and B is 0.90:0.10. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 30° C. and the reaction is continued for 2 h to obtain a polymer solution with a solid content of 4.0 wt % and a dynamic viscosity of 34,000 centipoise at 25° C.
[0070] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were subjected to continuous heat stretching treatment at 420° C. for 1 min, with a stretching tension of 0.05 cN / dtex and a nitrogen flow rate of 5 L / min, to prepare modified para-aramid fibers with a dechlorination degree of 10%. The fiber properties are shown in Table 1.
[0071] Example 7
[0072] A. In the first reactor, under the protection of dry nitrogen, diamine monomers PABZ (78.451 g) and PDA (9.187 g) were added to a composite solvent of N,N-dimethylacetamide with a mass fraction of 4% lithium chloride in a molar ratio of 0.70:0.17, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 10°C, and then TPC (81.207 g) with an equivalent weight of 92% to the diamine was added at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 24.0;
[0073] B. In another reaction kettle, under the protection of dry nitrogen, 2-(2-chloro-4-aminophenyl)-5-aminobenzoxazole (Cl-BOA, 16.872 g) was added to a N,N-dimethylacetamide composite solvent with a mass fraction of 4% lithium chloride, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 10°C, and then TPC (20.454 g) with an equivalent weight of 155% to Cl-BOA was added at one time. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer was obtained with a degree of polymerization of 4.6;
[0074] C. The molar ratio of the diamine monomers PABZ, PDA and Cl-BOA added in steps A and B is 0.70:0.17:0.13. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 30° C. and the reaction is continued for 1 hour to obtain a polymer solution with a solid content of 3.5 wt % and a dynamic viscosity of 96,000 centipoise at 25° C.
[0075] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were subjected to static heat treatment at 370° C. for 30 min under the protection of nitrogen at a flow rate of 1 L / min to obtain modified para-aramid fibers with a dechlorination degree of 14%. The fiber properties are shown in Table 1.
[0076] Example 8
[0077] A. In the first reactor, under the protection of dry nitrogen, add the diamine monomer PABZ (68.931 g) to the N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 3.0%, stir until the diamine is completely dissolved, lower the internal temperature to 8°C, and then add TPC (54.290 g) equivalent to 87% of the diamine at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution is obtained, and its degree of polymerization is 14.4;
[0078] B. In another reaction kettle, under the protection of dry nitrogen, add 2-(2-chloro-4-aminophenyl)-5-aminobenzimidazole (Cl-PABZ, 4.185 g) to N,N-dimethylacetamide composite solvent with a mass fraction of 3.0% lithium chloride, stir until the diamine is completely dissolved, lower the internal temperature to 8°C, and then add acyl chloride (11.265 g) equivalent to 343% of Cl-PABZ at one time. After reacting for 0.5 h, an acyl chloride-terminated chlorine-containing block oligomer with a degree of polymerization of 1.8 is obtained;
[0079] C. The molar ratio of the diamine monomers PABZ and Cl-PABZ added in steps A and B is 0.95:0.05. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 30° C. and the reaction is continued for 2 hours to obtain a polymer solution with a solid content of 4.0 wt % and a dynamic viscosity of 46,000 centipoise at 25° C.
[0080] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were subjected to continuous heat stretching treatment at 410° C. for 2 min, with a stretching tension of 0.2 cN / dtex and a nitrogen flow rate of 3 L / min, to prepare modified para-aramid fibers with a dechlorination degree of 9%. The fiber properties are shown in Table 1.
[0081] Example 9
[0082] A. In the first reactor, under the protection of dry nitrogen, diamine monomers PABZ (55.786 g) and PDA (9.607 g) were added to a N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.0% in a molar ratio of 0.7:0.25, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 8°C, and then TPC (61.205 g) with an equivalent weight of 89% to the diamine was added at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 17.7;
[0083] B. In another reactor, under the protection of dry nitrogen, add 2,5-dichloro-1,4-phenylenediamine (DCl-PDA, 3.146 g) to N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.0%, stir until the diamine is completely dissolved, lower the internal temperature to 8°C, and then add TPC (10.941 g) equivalent to 303% of DCl-PDA at one time. After reacting for 0.6 h, an acyl chloride-terminated chlorine-containing block oligomer with a polymerization degree of 2.0 is obtained;
[0084] C. The molar ratio of the diamine monomers PABZ, PDA and DCl-PDA added in steps A and B is 0.7:0.25:0.05. The chlorine-containing block oligomer terminated with acyl chloride in step B is poured into the first reaction kettle and stirred and blended with the chlorine-free block oligomer solution terminated with amino group. The temperature is raised to 30° C. and the reaction is continued for 2 hours to obtain a polymer solution with a solid content of 4.0 wt % and a dynamic viscosity of 82,000 centipoise at 25° C.
[0085] D. The polymer solution in step C was subjected to the same wet spinning process as in Example 1 to obtain modified para-aramid precursor fibers, and then the precursor fibers were placed in an atmosphere of 50 Pa vacuum, heated to 340° C. for 60 min for static heat treatment to obtain modified para-aramid fibers with a dechlorination degree of 10%. The fiber properties are shown in Table 1.
[0086] Comparative Example 1
[0087] The process is basically the same as that of Example 9, except that:
[0088] The TPC feed distribution in step A and step B is changed to change its polymerization degree. In step A, the TPC feed amount is 92% (63.056g) of the equivalent of diamine, and the polymerization degree of the chlorine-free block is 24.0. In step B, the TPC feed amount is 252% (9.090g) of the equivalent of DCl-PDA, and the polymerization degree of the chlorine-containing block is 2.3. The dechlorination degree of the modified para-aramid finished fiber finally prepared is 6%. The fiber properties are shown in Table 1.
[0089] Comparative Example 2
[0090] The process is basically the same as that of Example 9, except that:
[0091] The TPC feed distribution in step A and step B is changed to change its polymerization degree. In step A, the TPC feed amount is 65% (44.550g) of the equivalent of diamine, and the polymerization degree of the chlorine-free block is 4.7. In step B, the TPC feed amount is 765% (27.596g) of DCl-PDA equivalent, and the polymerization degree of the chlorine-containing block is 1.3. The dechlorination degree of the modified para-aramid finished fiber finally prepared is 5%. The fiber properties are shown in Table 1.
[0092] Comparative Example 3
[0093] The same molar ratio of diamine monomers as in Example 9 was used, that is, the molar ratio of PABZ, PDA and DCl-PDA was 0.7:0.25:0.05. The specific preparation process is as follows:
[0094] The chlorine-containing para-modified aramid was prepared by random copolymerization. Under nitrogen protection, PABZ (55.786 g), PDA (9.607 g) and DCl-PDA (3.146 g) were added to a composite solvent of N,N-dimethylacetamide with a mass fraction of 3.5% of lithium chloride, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 5°C, and TPC (64.932 g) accounting for 90% of the molar amount of the diamine was added first. After reacting for 1 hour, the temperature was raised to 30°C, and the remaining 10% of TPC (7.215 g) was added twice. The stirring reaction was continued for 2 hours to obtain a random copolymerized chlorine-containing para-modified aramid polymer solution with a solid content of 4.0wt% and a dynamic viscosity of 81,000 centipoise.
[0095] The wet spinning process and heat treatment process were the same as those in Example 9, and the dechlorination degree of the chlorine-containing modified para-aramid finished fiber finally prepared was 4%. The fiber properties are shown in Table 1.
[0096] Comparative Example 4
[0097] A. In the first reactor, under the protection of dry nitrogen, diamine monomers PABZ (61.238 g) and PDA (5.062 g) were added to a N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.0% in a molar ratio of 0.7:0.12, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 8°C, and then TPC (63.643 g) with an equivalent weight of 98% to the diamine was added at one time. After reacting for 1 hour, an amino-terminated chlorine-free block oligomer solution was obtained, and its degree of polymerization was 99.0;
[0098] B. In another reaction kettle, under the protection of dry nitrogen, DCl-PDA (12.431 g) was added to a N,N-dimethylacetamide composite solvent with a lithium chloride mass fraction of 4.0%, and stirred until the diamine was completely dissolved. The internal temperature was lowered to 8°C, and then TPC (15.554 g) with an equivalent weight of 109% to DCl-PDA was added at one time. After reacting for 0.6 h, an acyl chloride-terminated chlorine-containing block oligomer was obtained with a degree of polymerization of 23.0;
[0099] C. Pour all the chlorine-containing block oligomer terminated with acyl chloride in step B into the first reaction kettle and stir and blend with the chlorine-free block oligomer terminated with amino group. Raise the temperature to 30° C. and continue the reaction for 2 h to obtain a polymer solution with a solid content of 4.0 wt % and a dynamic viscosity of 78,000 centipoise at 25° C. The molar ratio of the diamine monomers PABZ, PDA and DCl-PDA in the polymer is 0.7:0.12:0.18.
[0100] D. The wet spinning process and heat treatment process were the same as those in Example 9, and the dechlorination degree of the chlorine-containing modified para-aramid finished fiber finally prepared was 22%. The fiber properties are shown in Table 1.
[0101] Comparative Example 5
[0102] Under nitrogen protection, PABZ (82.712 g) and PDA (17.093 g) were weighed in a molar ratio of 0.7:0.3, added to a composite solvent of N, N-dimethylacetamide with a mass fraction of 3.5% lithium chloride, stirred until the diamine was completely dissolved, the internal temperature was lowered to 5°C, TPC (96.272 g) accounting for 90% of the molar amount of the diamine was added first, reacted for 1 hour, heated to 30°C, and the remaining 10% of TPC (10.697 g) was added twice, and the stirring reaction was continued for 2 hours to obtain a common heterocyclic aramid polymer solution with a solid content of 3.5wt% and a dynamic viscosity of 65,000 centipoise; the wet spinning process and heat treatment process were the same as those in Example 9, and finally a common hybrid aramid finished yarn was obtained. The fiber properties are shown in Table 1.
[0103] The modified para-aramid prepared by the methods provided in Examples 1-9 and Comparative Examples 1-5 were tested for tensile properties, toughness and epoxy-impregnated yarn strength, and the test methods were as follows:
[0104] Tensile performance test: British Instron 4302 strength tester was used, according to GB / T19975-2005 standard, the clamping distance was 500mm, and the tensile speed was 250mm / min.
[0105] Toughness test: The toughness test of modified para-aramid is calculated by the integral area under the fiber stress (cN / dtex)-strain (%) curve. Figure 2 It can be seen that the higher the tensile strength and elongation at break, the greater the toughness.
[0106] Epoxy dipped wire strength test: using British Instron 4302 strength tester, according to GJB348-87 standard test.
[0107] The test results are shown in Table 1.
[0108] Table 1 Test results of tensile properties, toughness and epoxy resin impregnated wire strength
[0109]
[0110]
[0111] From the data in Table 1, it can be seen that compared with the existing common hybrid aramid in Comparative Example 5, Examples 1, 4, 5, 6, 7, 8 and 9 introduce chlorine-containing diamine monomers into the modified para-aramid by block copolymerization, and the strength and toughness of the modified para-aramid are significantly improved after heat treatment to dechlorinate and induce local chain extension of the chlorine-containing block, and have better composite properties. In addition, using the same precursor as in Example 1, in Example 2, a higher temperature static heat treatment (400°C) is performed, so that the degree of dechlorination is increased from 13% in Example 1 to 57%, and a lot of dechlorinated gas escapes and the molecular chain is thermally degraded, resulting in structural defects, from Figure 2 It can be seen that the tensile strength and elongation at break of the modified fiber are significantly deteriorated, and the toughness decreases; while in Example 3, due to the low heat treatment temperature (320°C), the degree of dechlorination of the chlorine side group is less than 1%, and the chain extension cannot be induced, and the tensile strength and toughness of the fiber are also low. After a large number of experiments, the appropriate static heat treatment temperature is 340-380°C, or the continuous heat stretching treatment temperature is 390-420°C. The polymerization degree ratio of the chlorine-free block and the chlorine-containing block has a key influence on the performance of the fiber. Compared with Example 9, the polymerization degree ratio in Comparative Example 1 is too large (10.4), and the polymerization degree ratio in Comparative Example 2 is too small (3.6). It can be seen that the tensile strength and toughness of the fiber are not high. In Comparative Example 3, the chlorine-modified para-aramid fiber is prepared by conventional random copolymerization. Compared with Example 9, it can be found that its strength and toughness are significantly lower. Comparative Example 4 uses a higher content of DCl-PDA for block copolymerization, wherein the molar ratio of DCl-PDA in the diamine is 18%. Although the polymerization degree ratio of the chlorine-free block and the chlorine-containing block is 4.3, the degree of dechlorination of the chlorine side groups reaches 22%. Compared with Example 9, the strength and toughness of the fiber in Comparative Example 4 also decrease. After a large number of experiments, it was screened out that the molar ratio of chlorine-containing diamine to all diamines is 0.05-0.15, and the fiber has good strength and toughness.
[0112] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing high-strength and high-toughness modified para-aramid fiber, characterized in that: The following steps are involved: S1. Under the protection of dry nitrogen, a diamine monomer is added to a lithium chloride N,N-dimethylacetamide composite solvent to dissolve, the reaction temperature is lowered to 0-10° C., and then terephthaloyl chloride equivalent to 75-97% of the diamine is added to react to obtain an amino-terminated chlorine-free block oligomer with a degree of polymerization of 7.0-65.7, wherein the diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole, or 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine; S2, under the protection of dry nitrogen, adding the chlorine-containing diamine monomer to a lithium chloride N,N-dimethylacetamide composite solvent to dissolve, lowering the reaction temperature to 0-10° C., and then adding terephthaloyl chloride equivalent to 115-400% of the chlorine-containing diamine to react to obtain an acyl chloride-terminated chlorine-containing block oligomer with a degree of polymerization of 1.7-14.3, wherein the molar ratio of the chlorine-containing diamine to all diamines in steps S1 and S2 is 0.05-0.15; S3, blending all the chlorine-free block oligomers of step S1 with all the chlorine-containing block oligomers of step S2, heating to 20-40° C. for reaction, to obtain a polymer solution having a solid content of 3-4.5 wt % and a dynamic viscosity of 30,000-100,000 centipoise at 25° C., wherein the polymerization degree ratio of the chlorine-free block oligomer to the chlorine-containing block oligomer is 4.0-9.0; S4, subjecting the polymer solution of step S3 to a wet spinning process to obtain a modified para-aramid precursor, and then subjecting the modified para-aramid precursor to a static heat treatment at 340-380° C., or a continuous heat stretching treatment at 390-420° C., so that the degree of breakage and removal of the chlorine side groups is 7-20%, and finally preparing a modified para-aramid fiber.
2. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In step S1, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 0.65-0.95:0-0.
25.
3. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In steps S1 and S2, the mass fraction of lithium chloride in the N,N-dimethylacetamide composite solvent is 3-5%.
4. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In steps S1 and S2, the total amount of terephthaloyl chloride added twice accounts for 0.995 to 1.005 of the total amount of diamines added in molar ratio.
5. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: The chlorine-containing diamine is at least one of 2-chloro-1,4-phenylenediamine, 2,5-dichloro-1,4-phenylenediamine, 3,3'-dichlorobenzidine, 2-chloro-4,4'-diaminobenzanilide, 2,6-dichloro-4,4'-diaminobenzanilide, 2-(2-chloro-4-aminophenyl)-5-aminobenzimidazole and 2-(2-chloro-4-aminophenyl)-5-aminobenzoxazole.
6. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In step S4, the static heat treatment process is carried out by vacuuming <200Pa or introducing 0.5-5L / min nitrogen for protection.
7. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In step S4, 0.5 to 5 L / min nitrogen is introduced during the continuous hot stretching process for protection.
8. The method for preparing high-strength and high-tenacity modified para-aramid fiber according to claim 1, characterized in that: In step S4, the tension of the continuous heat stretching is 0.05 to 0.5 cN / dtex.
9. A modified para-aramid fiber, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
High-performance chloric heterocyclic aramid fiber as well as preparation method and application
CN104357939A
Heterocyclic aramid fiber preparation method based on post-high-temperature chain extension reaction
CN106929938A
Chlorine-containing high-performance heterocyclic aromatic polyamide fiber and preparation method thereof
CN107779975A
Preparation method of surface sizing agent for aramid fiber composite material
CN111979775A
High-strength high-modulus heterocyclic aramid fiber and preparation method thereof
CN115678004A